Pimavanserin Treatment for Parkinson's Disease Psychosis in Clinical Practice. (4th January 2021) - Dashtipour, Khashayar; Gupta, Fiona; Hauser, Robert A.; Karunapuzha, Cherian A.; Morgan, John C.
Abstract : Background . Parkinson's disease psychosis (PDP) is a common, nonmotor symptom of Parkinson's disease (PD), which may affect up to 60% of patients and is associated with impaired quality of life, increased healthcare costs, and nursing home placement, among other adverse outcomes. Characteristic symptoms of PDP include illusions; visual, auditory, tactile, and olfactory hallucinations; and delusions. PDP symptoms typically progress over its course from being mild, infrequent, and often untroubling to complex, sometimes constant, and potentially highly disturbing. PDP has traditionally been treated with atypical antipsychotics (e.g., clozapine and quetiapine) although these are not approved for this indication and clozapine requires frequent white blood cell count monitoring due to the risk of agranulocytosis. Pimavanserin is a newer atypical antipsychotic with highly selective binding to serotonergic receptors, no evidence for worsening motor symptoms in PD, and no need for white blood cell count monitoring. It is currently the only approved medication indicated for PDP treatment. However, because it was approved relatively recently (2016), clinical experience with pimavanserin is limited. Case Presentations . A wide variety of representative clinical scenarios are presented, each with distinct variables and complications. Issues addressed include distinguishing PDP from similar symptoms caused by other disorders such as dementia, coordinating pimavanserin with other PD medications and with deep brain stimulation, adapting pimavanserin dosing for optimal benefit and tolerability, and recognizing variability of PDP symptoms due to patients' changing life circumstances. Conclusions . These scenarios provide multiple insights regarding PDP management and the role of pimavanserin. Effective treatment of PDP may reduce disturbing symptoms of psychosis, thus improving patient function and quality of life. In addition, effective pharmacotherapy for PDP may also facilitate the use of other medications needed to treat neurological symptoms of PD (e.g., tremor, bradykinesia, and dyskinesia), although they may also have adverse effects that contribute to symptoms of PDP.